2018
DOI: 10.1111/cdev.13027
|View full text |Cite
|
Sign up to set email alerts
|

Parental Depression, Overreactive Parenting, and Early Childhood Externalizing Problems: Moderation by Social Support

Abstract: This study used a large (N = 519), longitudinal sample of adoptive families to test overreactive parenting as a mediator of associations between parental depressive symptoms and early childhood externalizing, and parents' social support satisfaction as a moderator. Maternal parenting (18 months) mediated the association between maternal depressive symptoms (9 months) and child externalizing problems (27 months). Paternal parenting was not a significant mediator. Unexpectedly, we found a cross-over effect for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…Previous research has largely focused on the importance of parenting behavior and family environment as a mechanism linking maternal affective problems to externalizing problems in childhood [61][62][63]. The current study extended past work by identifying another possible mechanism through which maternal affective problems affect subsequent externalizing problems: by impairing offspring self-regulated compliance in early childhood.…”
Section: Discussionmentioning
confidence: 52%
“…Previous research has largely focused on the importance of parenting behavior and family environment as a mechanism linking maternal affective problems to externalizing problems in childhood [61][62][63]. The current study extended past work by identifying another possible mechanism through which maternal affective problems affect subsequent externalizing problems: by impairing offspring self-regulated compliance in early childhood.…”
Section: Discussionmentioning
confidence: 52%
“…High ratings on the sensitivity/responsiveness dimension indicate that mothers are able to observe and respond to the child's bids and social expressions as well as to their signs of frustration, confusion, and negative affect and to generally provide emotional support to the child (SECCYD; NICHD Early Child Care Research Network, 1999). These parenting behaviors are characteristic of sensitive child-centered interaction (Mills-Koonce et al, 2015;Taraban et al, 2018) and have been shown to play an important role in establishing quality in parent-child interactions (Barnett et al, 2010;Mills-Koonce et al, 2015;Tamis-LeMonda et al, 2004). It is noteworthy that the adoptive mothers in the current study acted as Our findings with regard to maternal sensitivity/responsiveness are in line with those of Juffer and Rosenboom (1997), who reported that adoptive and biological mothers showed the same level of sensitive-responsive behavior when solving a puzzle and making a drawing together with their child at ages 6 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…A vast literature shows that a warm and positive parenting style characterized by sensitivity and responsiveness is positively related to children's behavior and adaptation, whereas controlling, intrusive, and punitive parental behavior adversely affects developmental outcomes (e.g., Campbell et al, 1996;Shaw et al, 2000;Taraban et al, 2018). In particular, when parents are sensitively engaged in communication and play and offer stimulating interactive surroundings, children show better social, emotional, and cognitive development (Mills-Koonce et al, 2015).…”
mentioning
confidence: 99%
“…However, empirical evidence has been mixed. On the one hand, several studies have reported social support as a protective role in child socioemotional outcomes by weakening the negative effects of less optimal parenting behaviors (Crnic, Greenberg, & Slough, 1986; Heberle, Krill, Briggs‐Gowan, & Carter, 2015; Meunier, Wade, & Jenkins, 2012; Taraban et al, 2019). Onthe other hand, others failed to identify significant moderation effects between parenting/parent–child interaction and parent perceived social support in predicting young children's developmental outcomes (Mills‐Koonce et al., 2016; Oravecz et al., 2008).…”
Section: Introductionmentioning
confidence: 99%